Performance and Emission of Low Speed IDI Diesel Engine by Using Pure Plant Oil as Fuel in Hybrid Power Generation System (DieselSolar - Eko Harjono, Jalu
Hybrid power electric generator system is one of suitable power generator used in remote islands in Indonesia. Hybrid power electric generator system usually use renewable energy source such as solar power, hydro power, and wind power that combined with unrenewable energy source such as diesel generator. This research is looking for performances and emissions of IDI diesel engine combined with solar panels in the hybrid power electric generator system that use pure vegetable oil as fuel. Because in remote island, there are plenty of plant that can be used as vegetable oil. The performance test result shows that hybrid power generator system consumes less fuel on average of 7% compared to stand alone diesel generator. Therefore the diesel generator in hybrid power generator system consume more fuel on average of 29% compared to stand alone diesel generator. The emissions test result shows that hybrid power electric generator system produces carbon dioxide emissions lower on average 30.8% and the opacity of smoke lower on average of 32.2% compared to stand alone diesel generator.